2021
DOI: 10.3390/molecules26195888
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Multiplication and NMR Fingerprinting of Rare Veronica caucasica M. Bieb

Abstract: Micropropagation of rare Veronica caucasica M. Bieb. was achieved by successful in vitro cultivation of mono-nodal segments on MS medium supplemented with 1.0 mg L–1 6-benzylaminopurine (BA) and then transferring the regenerated plants on hormone free basal MS medium for root development. In vitro multiplicated plants were successively acclimated in a growth chamber and a greenhouse with 92% survival. The number of plastid pigments and the total phenolics content in in vitro cultivated and ex vitro adapted pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Benzyladenine has been successfully applied to increase the growth coefficient in other in vitro cultivated endemic species as well. In Achillea thracica and Veronica caucasica , 1 mg/L of BA stimulated growth under in vitro conditions, while in Verbascum eriophorum , 0.5 mg/L of BA stimulated the formation of 14.22 ± 0.2 shoots, without vitrification or callus formation being observed [ 23 , 24 , 25 ]. Panayotova et al [ 26 ] and Mantovska et al [ 11 ] reported the initiation of in vitro cultures of S. maritima and S. thracica where low seed germination was observed, but robust growth occurred on the medium without added growth regulators.…”
Section: Resultsmentioning
confidence: 99%
“…Benzyladenine has been successfully applied to increase the growth coefficient in other in vitro cultivated endemic species as well. In Achillea thracica and Veronica caucasica , 1 mg/L of BA stimulated growth under in vitro conditions, while in Verbascum eriophorum , 0.5 mg/L of BA stimulated the formation of 14.22 ± 0.2 shoots, without vitrification or callus formation being observed [ 23 , 24 , 25 ]. Panayotova et al [ 26 ] and Mantovska et al [ 11 ] reported the initiation of in vitro cultures of S. maritima and S. thracica where low seed germination was observed, but robust growth occurred on the medium without added growth regulators.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro root formation can occur either autonomously or by induction. While some explants do not require plant growth regulators for root regeneration, many depend on exogenous hormones to induce rooting [18,19]. The use of different radiation sources has recently made available new choices for rooting in in vitro explant culturing.…”
Section: In Vitro Persian Violet Root Initiationmentioning
confidence: 99%